High pressure rheology and the impact on process homogeneity - Baars, Albert; Rauh, Cornelia; Delgado, Antonio (High Pressure Research, 2007)
The impact of different viscous substances on homogeneous thermal treatment during high pressure processes is exemplified for a cylinder piston system. Therefore, the relevant equations of thermofluid dynamics have been examined and conditions for homogeneous thermal processing have been set up. Furthermore, the analysis of an n-order inactivation kinetic delivers criteria for insensitivity of reactions to spatial temperature heterogeneities. The findings have been applied to a short time high pressure process and compared with results of numerical simulations. Good agreement could be achieved.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.highpr
Keywords: High pressure; Inactivation kinetic; Process homogeneity; Short time high pressure process; Viscosity